IMPLEMENTASI PERATURAN DAERAH NOMOR 11 TAHUN 2000 TENTANG PENGATURAN DAN PEMBINAAN PEDAGANG KAKI LIMA DI KOTA SEMARANG - Irzan Maulana Setyawan; Zaenal Hidayat; Dewi Rostyaningsih (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2013)
The existence of street vendors often considered as an illegal because it occupying publicspaces and its selling at the edge of Semarang highway. In Indonesia, especially the area ofSemarang City, the Government has made a Regional Regulation No. 11 of 2000 on Regulationand Development of Street Vendors to resolve the existing problems of street vendors inSemarang.The purpose of research is to analyze how the implementation of the Regional RegulationNo. 11 Of 2000 on Regulation and Development Street Vendors in Kokrosono Street Semarangand to analyze what makes the implementation of the Regional Regulation No. 11 Of 2000 onRegulation and Development street vendors in Kokrosono Street has not run as expected.According to George Edward III, he asserts that to consider four key issues in order to be aneffective policy implementation is to look at communication, resources, disposition, organizationalstructure. This research uses the exploratory qualitative type with the respondent from MarketOfficer and Kokrosono Street Vendors. The data sources of this study is primary and secondarydata, the data collection techniques used were interviews, documentation, observation. The dataquality that used in this study is the technique of triangulation data.Overall, the results of this study are the implementation of Regulation No. 11 of 2000 isnot running as expected. It can be seen from the accuracy of implementation and precision of thetarget policy is running well, but the accuracy of the process is still problematic. It can be seenfrom the accuracy of the implementation process, those Kokrosono street vendors aren’tunderstand, accept, and ready to implement this policy yet. And it can be seen with still manystreet vendors who sell on the roadside. The causes of this unexpected result are from thecommunication, resources, and disposition factors. Advice from researchers is to multiply thecommunication, increase the number of human resources, and do collaboration with theassociation chairman, local district to conduct surveillance.